2007
DOI: 10.1080/10401230701334747
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Change as a Predictor of Treatment Response in Obsessive Compulsive Disorder

Abstract: Preliminary findings indicate that greater resistance to change is associated with less improvement in OCD symptom severity following pharmacotherapy. As this is the first use of the URICA as a predictor of OCD response, future research should further examine the role of motivation to change in treatment outcome in a larger OCD sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
2
14
2
Order By: Relevance
“…The CQ self-report measure fared particularly well, with higher scores on this measure being associated with lower post-treatment worry and greater subsequent homework compliance (although the homework compliance effects were only marginally significant). These findings are somewhat incongruent with other studies examining various self-report motivation measures which generally find weak and inconsistent relationships with outcomes (Field, Adinoff, Harris, Ball, & Carroll, 2009; Kampman et al, 2008; Pinto, Pinto, Neziroglu, & Yaryura-Tobias, 2007; Sutton, 2001). Thus, if future research can replicate these findings, it suggests that the CQ may be a more promising self-report measure of motivation.…”
Section: Discussioncontrasting
confidence: 98%
“…The CQ self-report measure fared particularly well, with higher scores on this measure being associated with lower post-treatment worry and greater subsequent homework compliance (although the homework compliance effects were only marginally significant). These findings are somewhat incongruent with other studies examining various self-report motivation measures which generally find weak and inconsistent relationships with outcomes (Field, Adinoff, Harris, Ball, & Carroll, 2009; Kampman et al, 2008; Pinto, Pinto, Neziroglu, & Yaryura-Tobias, 2007; Sutton, 2001). Thus, if future research can replicate these findings, it suggests that the CQ may be a more promising self-report measure of motivation.…”
Section: Discussioncontrasting
confidence: 98%
“…Measures of motivation collected during the first 4 to 6 weeks of therapy significantly predicted improvement, consistent with some studies (e.g., [10, 11, 33]; but see [34]). However, the relationship between motivation and outcome was not linear.…”
Section: Discussionsupporting
confidence: 85%
“…Clinical experience suggests that patient motivation is a critical prerequisite for treatment success, particularly in intensive ERP (e.g., [32]). Indeed, several studies have found that motivation predicted positive treatment outcome in both CBT and pharmacotherapy for OCD (e.g., [10, 11, 33]; but see [34]), and at least two studies are in progress to investigate the utility of adding motivational enhancement techniques to improve outcome [35, 36]. In addition, some have argued that a sizable portion of variance in treatment effects can be attributed to patient expectations (e.g., [37]).…”
mentioning
confidence: 99%
“…Vogel et al [3] found that readiness to change showed no relation to treatment outcome for 37 outpatients treated with cognitive-behavioral therapy. A similar study conducted by Pinto et al [4] found a negative association between precontemplation and change in OCD symptoms using a sample of 32 outpatients receiving pharmacotherapy. In another outpatient study (n = 28), Maher et al [5] found no significant relationship between readiness to change and cognitive-behavioral treatment outcome.…”
Section: Tablementioning
confidence: 89%